The European Union's (Eu) Contribution As A Global Defense And Security Actor In The International System - Sudaryono, Sudaryono; Manurung, Hendra; Pannyiwi, Rahmat (JIMAD : Jurnal Ilmiah Multidisiplin, 2024)
History indeed has finally caught up with Europe. The European continent’s long period of relative peace from 1945 to 2022 was suppose an aberration. In any European capital today, the mood seems starkly different than before Russia invaded Ukraine on February 24, 2022. Suddenly, from Berlin to Brussels, leaders are racing to resuscitate their defence infrastructure and update their militaries capabilities which each dependent for too long on a U.S. security umbrella that is no longer guaranteed its sustainability. Despite the gravity of the moment, Europe’s attempts to put up a united front are like a pail with several leaks: In Belgrade, Bratislava, and Budapest, leaders friendly to the Kremlin have ridden a wave of disinformation and fearmongering to get elected or stay in power through one side propaganda. Meanwhile, the success of far-right parties in the European Parliament elections in June 2024 only added to fears about the continent’s regional stability. This research revealed Europe’s hand weakens will impact the rest of the world look to divide and conquer the European continent sooner or later.